Dynamics of Application of Social Sciences Subjects in the Independent Curriculum at Junior High School Level - Evi irdawanti Anjasmira; Syamsu Kamarrudin; A Octamaya Tenri Awaru (JURNAL PENDIDIKAN IPS, 2024)
The Merdeka Curriculum emphasizes students' freedom to explore themselves while making the teacher a partner in the learning process. This article will examine the dynamics of implementing social science subjects in the independent curriculum at junior high school level. The approach applied in this research is qualitative using online observation and document data collection techniques. Meanwhile, data analysis was carried out using a content analysis approach. The results of this research concluded that Social Sciences learning outcomes in the independent curriculum in junior high schools were made by referring to National Education Standards, especially Content Standards, as a reference in the learning process. Implementation stages using independent curriculum teaching modules at the junior high school level as well as ensuring sustainability and carrying out in-depth analysis in its implementation. In implementing it in schools, the obstacles for social studies teachers in implementing the independent curriculum are very diverse. This research reveals that the implementation of the independent curriculum is very dependent on school and teacher policies in implementing it, especially in social studies subjects, becoming an integration umbrella for various branches of social sciences and humanities disciplines to strengthen the competence of students. to have insight and skills in thinking, acting and having concern for the nation and society, where social studies subjects consist of history, sociology, economics and geography.